PENGARUH INOVASI DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI PRODUK BARU PADA PT. PRAPTA MAKASSAR - Erniati Erniati; Buyung Romadhoni; Andi Mappatompo (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
This study aims to determine the extent of the influence of innovation and product quality on customer satisfaction through new products. This type of research uses a quantitative approach. Data collection techniques through online questionnaires to 180 respondents. Hypothesis testing uses path analysis with the help of AMOS 21 software.The results showed that the innovation variable had a significant positive effect on new products; Product quality has a significant positive effect on new products; Innovation has a significant positive effect on customer satisfaction; Product quality has no significant positive effect on customer satisfaction; New products have a significant effect on customer satisfaction; Innovation has a significant positive effect on customer satisfaction through new products and product quality has a significant positive effect on customer satisfaction through new products. Keywords: Innovation, Product Quality, Customer satisfaction, New produduct.